Change of graphene with various strategies for photocatalytic applications: A Review - Won-Chun Oh (Jurnal Rekayasa Proses, 2020)
Because of its novel molecular 2D structure and momentous physicochemical properties, graphene has been started a whirlwind of the investigation into its optical, electronic, thermal, and mechanical properties. Specifically, a lot of considerations have been pulled in to investigate graphene and graphene composites for photoelectrochemical applications. Many works have been done to synthesize novel graphene-based materials for applications in photoelectrochemistry, such as photoelectrochemical sunlight-based cells, photocatalytic disintegration of natural contaminations, and H2 production. In this article, we abridge the condition of research on graphene-based materials for photoelectrochemistry. The prospects and further improvements in this energizing field of graphene-based materials are additionally discussed.